Modeling and Determination of a Nanocomposite Synthesized Hybrid Graphene Oxide Absorbents Properties for removal of Ni (II) from an Aqueous Solution Enhanced by a Hand held Magnet - ساناز فتحی; علیمراد رشیدی; ROSHANAK REZAEI KALANTARY; عبدالرضا کرباسی (مهندسی منابع آب, 2019)
The purpose of this study was a quick and easy separation  of Ni(II) from an aqueous solution by a hand-held magnet to prevent secondary pollution. Morphology and other structures of NPG@Fe3O4 were characterized by the  SEM and XRD techniques. The amount of optimal adsorption factors determined by carrying out 96 tests. The effect of various parameters on the absorption processes such as pH, contact time, adsorbent dosage, temperature and initial concentration in the reduction of contaminant concentrations were considered. The results showed that the optimum pH was 6.0, the optimal contact time was 30 minutes and the optimum adsorbent dosage was 50 mg/L. Adsorption isotherm models studied by both the Langmuir and the Freundlich isotherms was also followed by both the pseudo-first and second order models. The results also indicated that the showed adsorption process best fitted to Freundlich isotherm and pseudo-second order kinetic models. The Thermodynamic studies reviled that the adsorption process was endothermic and spontaneous. The maximum absorption capacity 82.25 mg/g indicated the optimal absorption of nickel from water by the synthesized nano adsorbent from graphene oxide.